On Regular generalized star b closed sets in bitopological spaces - K.Indirani, G.Sindhu (Asian Journal of Current Engineering and Maths, 2014)
The aim of this paper is to introduce the concepts of Ï„1Ï„2-Regular generalized star b closed and Ï„1Ï„2-Regular generalized star b open sets and study their basic properties in bitopological spaces. Also we introduce the concepts of pairwise rg*b-continuous mappings, RG*B-connectedness and RG*B-compactness in bitopological spaces and some of their properties are established.